Racing toward the future of chronic hepatitis B management: Achieving functional cure and enhancing hepatocellular carcinoma surveillance through precision medicine - Yaru Shi; Rong Fan (Interdisciplinary Medicine, 2025)
Abstract Hepatitis B virus (HBV) infection represents a significant global public health threat, often progressing to severe complications such as liver cirrhosis and hepatocellular carcinoma (HCC). Despite the World Health Organization’s 2030 challenge to eliminate HBV, achieving a functional cure remains a major milestone in the fight against the disease. However, even with functional cure, the risk of HCC persists, necessitating ongoing surveillance. Hopefully, advances in technological innovations, artificial intelligence, and the establishment of data platforms have enhanced both functional cure prediction and surveillance strategies. This review examines recent advancements in HBV therapies, prediction models for chronic hepatitis B (CHB) functional cure (such as the GOLDEN model) for evaluating these new approaches, and the current state of HCC surveillance. Furthermore, the potential of novel biomarkers is highlighted in the context of precision medicine to improve CHB functional cure and HCC risk assessment.